Swearing Words in “Celebrity Read Mean Tweets” in Jimmy Kimmel Late Night Show : A Sociolinguistic Study - Rezky Surya Darma; Wennyta Wennyta; Nurul Fitri (Universitas Batanghari Jambi, 2017)
AbstractHistorically, swearing is assumed as a form of the curse but since the sexual revolution happens in 1960, swearing not only used as a form of cursing, it can be used as a form of insult, emphasis, or even strengthen the bond between friends and co-worker. A Sociolinguistic analysis of swearing words in Celebrity read mean tweets purposes is to find out types and functions of swearing based on the meaning of the word. The data is gotten from the tweets in celebrity read mean tweets. The design of this research is qualitative research. For collecting the data, the researcher retypes all the swear words found in the celebrity read mean tweets with left the tweet without swear words, change the data from video into the word file. Then, the technique for analyzing the data was by pointing out the swear words and describing its meaning with the dictionary. The researcher has also categorized the type and function from the highest to the lowest. In the end, the result was found is sex swear words are the most frequent type of swearing and abusive swearing is the most frequent function of swearing. The conclusion is many of the cursing in religious terminology is changed with sex, and people cursing with sex swear words. Also, the gender-based swear words not only uttered based on the sex addresse, but can be also addressed by its opposite sex because the gender-based swear words can be used as the epithet for people. And the last is the swear words can be used as adjective, noun or adverb without following the grammatical rules from these three subject, because of the wide-usage of swear words.Keywords: Swearing words, Social media